Performance Analysis Of Solar Water Heating System With Plate Collector Integrated Pcm Storage - Andi Syahrinaldy Syahruddin; Jalaluddin Jalaluddin; Azwar Hayat (EPI International Journal of Engineering, 2020)
Availability of solar energy as a renewable energy source is very abundant and inexhaustible. Solar water heater is an equipment that utilizes solar energy as a source of energy. The thermal performance of a solar water heater system using absorber plate with phase change material (PCM) as thermal energy storage is presented in this study. Two design of solar water heater collectors with absorber plate variations, i.e. an absorber plate with PCM storage and absorber plate without PCM storage were investigated experimentally and numerically simulation. First, the material properties of paraffin wax as PCM storage was analized analyticaly. Every shape model of solar water heater systems were imported and simulated at three variations of constant solar radiation, i.e. 400 W/m2, 700 W/m2, and 1000 W/m2. The simulation using a computational fluid dynamic (CFD) fluent software. The results showed that the average collector efficiency between absorber plate with and without PCM storage is 70.98 % using experimental study and 67.73 % using numerical simulation study.